Development and Evaluation of a Real-Time Phase-Triggered Stimulation Algorithm for the CorTec Brain Interchange - Hanbin Cho; Moaad Benjaber; C. Alexis Gkogkidis; Marina Buchheit; Juan F. Ruiz-Rodriguez; Benjamin L. Grannan; Kurt E. Weaver; Andrew L. Ko; Steven C. Cramer; Jeffrey G. Ojemann; Timothy Denison; Jeffrey A. Herron (IEEE, 2024)
With the development and characterization of biomarkers that may reflect neural network state as well as a patient’s clinical deficits, there is growing interest in more complex stimulation designs. While current implantable neuromodulation systems offer pathways to expand the design and application of adaptive stimulation paradigms, technological drawbacks of these systems limit adaptive neuromodulation exploration. In this paper, we discuss the implementation of a phase-triggered stimulation paradigm using a research platform composed of an investigational system known as the CorTec Brain Interchange (CorTec GmbH, Freiburg, Germany), and an open-source software tool known as OMNI-BIC. We then evaluate the stimulation paradigm’s performance in both benchtop and in vivo human demonstrations. Our findings indicate that the Brain Interchange and OMNI-BIC platform is capable of reliable administration of phase-triggered stimulation and has the potential to help expand investigation within the adaptive neuromodulation design space.